Urgenza e legalità ai tempi del CoViD-19: fra limiti imprescindibili e necessaria flessibilità (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
In order to cope with the CoViD-19 epidemic, the Italian Government approved two Decree-law, later ratified by Parliament, conferring the Prime Minister the power to adopt the regulation to implement the social distancing measures. The essay deals with the compatibility of such a normative method with the Italian Constitution, in particular with the principles concerning the exercise of the legislative power by the Government in emergency situations (art. 77) and the freedom of movement enshrined by art. 16 of the Italian Basic Law.
Keywords: CoViD-19; pandemic emergency; emergency powers; executive; freedom of movement